Eros and the Christ : longing and envy in Paul's christology - Fredrickson, David E. (David Earl) (Minneapolis : Fortress Press, 2013)
"The self-emptying of Christ (kenosis) in Philippians 2 has long been the focus of attention by Christian theologians and interpreters of Paul's christology. David E. Fredrickson sheds dramatic new light on familiar texts by discussing the centuries-old language of love and longing in Greek and Roman epistolary literature, showing that a "physics" of desire was related to notions of power and dominance. Paul's kenotic Christology challenged not only received notions of the power of the gods but of the very nature of love itself as a component of human society"--P. [4] of cover.
Series statement on jacket.
Includes bibliographical references (p. 159-173) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Love -- Biblical teaching; Love -- Religious aspects -- Christianity; Desire -- Religious aspects -- Christianity